The Inflammatory Bone Marrow Milieu: An Association Between CML Disease Activity, Systemic Inflammation, and Bone Turnover Independent of Vitamin D - Fayyadh, Mohammed Amer; Ahmed, Waleed Khalid; Mohammed Atiyah Al-Mohammadi, Wissam Mahmood; Yasin, Youssef Shakuri; Jumaa, Azal Hamoody (Asian Pacific Journal of Cancer Biology, 2026)
Background: Metabolic bone disease is a recognized complication of Chronic Myeloid Leukemia (CML), often linked to tyrosine kinase inhibitor (TKI) therapy or vitamin D deficiency. The ‘Inflammatory Bone Marrow Niche’ hypothesis suggests the leukemic microenvironment may independently disrupt bone metabolism. Objective: To investigate whether markers of chronic myeloid leukemia (CML) disease burden, such as lactate dehydrogenase (LDH), and markers of inflammation and iron homeostasis, including ferritin and interleukins, are associated with bone turnover markers parathyroid hormone (PTH) and alkaline phosphatase (ALP) after controlling for vitamin D levels. Patients and Methods: This retrospective cross-sectional study involved 90 adult patients with chronic myeloid leukemia (CML) who were receiving tyrosine kinase inhibitor (TKI) therapy for at least 12 months at the Oncology Teaching Hospital, Baghdad, Iraq. Data were collected from January to September 2024 through patient records, measuring serum levels of vitamin D3, LDH, ferritin, PTH, and ALP. An inflammatory score was calculated using IL-6 and IL-1β, and multiple linear regression analyses were performed to identify independent associations. Results: Multiple linear regression analysis identified lactate dehydrogenase (LDH) (β=0.35, p=0.003) and the inflammatory composite score (β=0.28, p=0.012) as significant, independent predictors of elevated alkaline phosphatase (ALP). Furthermore, ferritin levels were found to be a significant positive predictor of parathyroid hormone (PTH) levels (β = 0.31, p = 0.008). These associations remained statistically significant after adjusting for vitamin D3, which did not emerge as a significant predictor in either model. Conclusion: This study provides a novel perspective, suggesting the leukemic microenvironment may be a key contributor to bone dysregulation in CML. The findings challenge traditional paradigms by indicating that bone health may also be influenced not only by calcium homeostasis and drug toxicity but also by disease-related molecular interactions. Monitoring inflammatory biomarkers could enhance risk stratification, facilitating comprehensive management of hematological and skeletal health.